Treatment and management of maladaptive schemas - Kreuter, Eric A. (Springer International Publishing, 2014)
Praise for Treatment and Management of Maladaptive Schemas:   "This groundbreaking book helps mental health practitioners (as well as anyone else who reads it) identify and change their clients' maladaptive schema into those that are positive, life-affirming, and adaptive. It also presents an original paradigm of consciousness that encompasses all areas of human growth and development, healthy and unhealthy, wise and downright stupid." Stanley Krippner, Ph.D. Professor of Psychology, Saybrook University   "This book provides...a context and vocabulary to understand and ultimately suggest ways to alleviate the negative consequences of traumatic events on our lives." Brendan D. Leonard, M.B.A. Fellow Former Trustee with Eric Kreuter, Saybrook University   Treatment and Management of Maladaptive Schemas offers innovative means of altering self-destructive beliefs and their resulting behaviors. Likening change in individuals' entrenched ways of organizing the world to paradigm shifts in science, this path-breaking volume models cognitive therapy and counseling that is both schema-focused and strengths-based. This framework spans toxic schemas in relationships, positive and negative uses of spirituality, bedrock client skills including realistic goal-setting and overcoming impasses and fears, and key therapist skills such as assessing problems, bonding effectively with clients, and evaluating progress. And for maximum utility, chapter synopses identify key concepts, case summaries translate technique into practice, and appendices provide helpful tools and creative insights. Included in the coverage:   Paradigms and maladaptive schemas. Schema-focused cognitive therapy. How do we define success? The source of paradigmatic thinking. Catalyzing the hidden inner strength toward exploration. Clients who shifted paradigms: case examples.   Offering fresh possibilities for client hope and confidence, Treatment and Management of Maladaptive Schemas opens up new therapeutic avenues for clinicians and professional coaches, as well as students of behavioral psychology and human resource professionals.